Comparison of two antimicrobial regimens on the prevalence of incisional infections after colic surgery. (16th March 2013) - Durward‐Akhurst, S. A.; Mair, T. S.; Boston, R.; Dunkel, B.
Abstract : Appropriate durations of perioperative antimicrobial therapy following exploratory coeliotomy in horses are controversial, and with the rising prevalence of multiresistant bacteria there is a strong incentive to use antimicrobials for the shortest time possible. Following exploratory coeliotomies, incisional infections are an important cause of morbidity in horses and could be influenced by the duration of systemic antimicrobial therapy. The aim of this study was to investigate whether 72 hours of perioperative antimicrobial therapy is as effective as 120 hours at preventing the development of postoperative incisional infections. Horses undergoing exploratory coeliotomy at two referral hospitals were assigned randomly into Group 1 (receiving 72 hours of perioperative antimicrobial therapy) and Group 2 (receiving 120 hours of perioperative antimicrobial therapy). Only horses recovering from surgery and surviving for >120 hours were included in the study. Ninety‐two horses met the criteria for inclusion in the study, 42 in Group 1 and 50 in Group 2. The overall incisional complication rate was 42.2 per cent, and no significant difference in the number of incisional complications in the two groups was identified. Results of the study suggest that there is no benefit in using 120 hours over 72 hours of perioperative antimicrobial therapy to prevent incisional infections.